Antecedents of subjective severity of detention and perceived procedural justice - Yasrebi-de Kom, Franziska M. (Psychology, crime & law, 2024)
In this paper, we study what factors contribute to the extent that detained individuals (a) perceive their time in detention as severe and (b) perceive their treatment by prison staff as procedurally just. More specifically, the aim of the study is to examine the antecedents of subjective severity of detention (SSD) and perceived procedural justice (PPJ) with the aim to identify individual and situational characteristics that contribute to such perceptions. Our analyses were based on data from the Prison Project (n = 1430), which includes detailed information on measures of SSD, and PPJ among Dutch males held in Dutch penitentiary institutions. Based on their SSD and PPJ scores, detained individuals were classified as belonging to one of four subgroups (reference group, high SSD, high PPJ, or high both). Using a large set of background variables, we found that older age, a less elaborate criminal history, no daily drug use before arrest, not having experienced any victimization by prison staff, and the personality traits of neuroticism, conscientiousness, and agreeableness were the most relevant antecedents for ‘high both’ subgroup membership.